Handbook of perception and action, three volume set - Neumann, Odmar; Sanders, A. F. ([S.l.] : Academic Press, 1996)
The Handbook of Perception and Action overviews state-of-the-art research in these two areas, while also stressing the functional relationships between them. The three-volume set will be useful toresearchers, technicians, graduate students, and final-year undergraduates in psychology, developmental psychology, speech and hearing, neuropsychology, neuroscience, and physiology.
vol. 1. Perception. -- vol. 2. Motor skills. -- vol. 3. Attention.